Estudio de turmalinas y su implicancia genética en cuerpos pegmatoideos del Cerro Guacho, sierras septentrionales de la provincia de Buenos Aires - Lajoinie, María Florencia (2013)
In the Cerro Guacho, Sierras Septentrionales of the Buenos Aires province, the complexity of the relationships between igneous and metamorphic processes difficults to establish the origin of the pegmatoid bodies with feldspar + plagioclase + quartz + tourmaline, located on the western flank of this hill. Petrographic, mineralogic and chemical studies (X-ray diffraction, FTIR spectroscopy, SEM and EDAX microscopy) indicate that the tourmaline of these bodies corresponds to the Schorl variety. According to compositional diagrams, these tourmalines come from Li-poor granitoids and pegmatites. The establishment of the origin of the tourmaline-bearing bodies contributes to the understanding of the geological history of the Precambrian basement.